Generative AI for Academic Publishing? Some Thoughts About Epistemic Diversity and the Pursuit of Truth - Ma, Lai (KULA, 2024)
The uses of generative AI have prompted both positive and negative responses. This short commentary contemplates potential issues concerning bibliodiversity, epistemic diversity, and data surveillance. It also cautions the potential erosion of public trust in academic publishing in the age of generative AI. Invoking the Sokal hoax, the commentary sheds light on what it means when knowledge, experience, expertise, and the pursuit of truth are on the line.